Glass Medallions of the Early Middle Ages of Termez - Bobomuratovna, Mamataliyeva Surayyo (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is dedicated to the glass medallions found in the Palace of the Termez Shahs. It is based on Zhukov’s scientific work. Numerous archeological excavations carried out in the territory of Old Termez in the last XX century have provided new information about the real creative people of this country and the kings of revenge for luxury. This century was a period of the appearance of palaces, the introduction of various scientific innovations in the field of decoration. The article describes the technological process of making glass medallions and their classification into groups on the basis of sources.